Geochemical and petrological characterization of the Singkut caldera-forming eruption (North Sumatra) - Yeo, Yue (Nanyang Technological University, 2020)
Little is known about the Singkut caldera in North Sumatra, despite its close proximity to the famous Toba caldera complex as well as to the capital city of Medan, which could possibly pose a threat to the population. To characterize the Singkut caldera-forming eruption, we constrained the intensive magmatic variables (temperature, T; pressure, P; oxygen fugacity, fO2; dissolved water content in the melt, H2Omelt) in the pre-eruption storage chamber and identified possible magmatic processes. This was done by investigating the petrography, bulk rock and glass geochemistry and mineral chemistry of the erupted products from Singkut (pre-caldera lava, caldera pumice and post-caldera lava). Thereafter, we applied several commonly used thermobarometers and hygrometers to calculate the possible ranges of each intensive variable. The high crystallinity (~ 40% observed in the pumices) of the erupted products suggest they originated from a crystal mush. Although the bulk rock compositions of the erupted products fall within the andesitic field, the glass compositions from the pumice samples are highly rhyolitic (> 77 wt% SiO2), indicating the highly silicic nature of the crystal mush. We found that the pre-caldera lava and caldera pumices are very similar in their geochemistry and mineral chemistry while the post-caldera lavas are more mafic. In addition, the post-caldera lavas vary in their extent of maficity— the early post-caldera lavas are compositionally similar to the pumices and pre-caldera lava while the late post-caldera lavas are more mafic. Overall, we obtained temperatures ranging from ~800 to 1000°C, pressures of ~100 to 240 MPa, oxygen fugacity of ~ +0.40 to +2.10 (relative to NNO) and H2Omelt of ~ 4 to 6.7 wt% H2O. We noted that while the estimated intensive variables of the post-caldera lavas fall within this range, they have higher temperatures and pressures and are slightly less oxidised than the pre-caldera lavas and caldera pumices, this is especially so for the late post-caldera lavas. Combining all our findings, we suggest the presence of a common crystal mush system in the shallow upper crust (~ 4 to 9 km) which was highly crystalline and rheologically locked. We propose that mafic recharge heated and melted low-temperature mineral phases in the crystal mush, as seen from the embayed and very scarce appearance of quartz, thus remobilizing the crystal mush and initiating the pre-caldera volcanism. The mafic recharge, heating and crystal dissolution could have subsequently remobilized a larger portion of the crystal mush, resulting in the caldera-forming eruption. In the post-caldera stage, the mafic recharge could have persisted and magma mixing could have occurred. This is supported by the more mafic nature of the late post-caldera lavas as well as the complex compositional zoning of the plagioclase which suggests multiple episodes of crystallization of more anorthite-rich plagioclase. Similarities in the geochemistry and mineral chemistry between Singkut, Toba and Sinabung, as well as geophysical information of the Toba and Sinabung areas also suggest that these three magmatic systems are possibly related.